The religion in higher education curriculum referring to Indonesian qualification framework: The inclusion of neuroscience and anti-corruption education - Suyadi Suyadi; Zalik Nuryana; Sutrisno Sutrisno (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
The research aims to develop the curriculum of the Higher Education Curriculum, specifically Islamic religion, referring to the Indonesian National Qualification Framework (KKNI). The problem raised in this research is the redesign of the curriculum in Indonesia, especially the formation of new courses such as the neuroscience of Islamic education and anti-corruption education, which have not considered the breadth of study material and calculation semester credit units that are not accountable. This research was conducted in three stages: curriculum analysis, curriculum matrix design, and curriculum matrix experimentation. The research subjects involved 133 lecturers in the Higher Education Institutions of Religion, both Islamic, Catholic, and Hindu in Indonesia. The findings indicate that the developed matrix design can be used as an integrative tool for forming subjects and calculating semester credit unit weights in a mathematical and accountable manner, and accommodating the development of Islamic education, particularly neuroscience and anti-corruption education. This matrix can complement Kim's research on syllabus ontology identification and lesson study innovation developed by E. Purwaningsih and D. Nurhadi.